COMPARISON OF THE BLACK CAT MYTH IN AMERICA AND IN INDONESIA THROUGH THE NOVEL "THE BLACK CAT" BY EDGAR ALLAN POE - Muhandra, Aisyah Putri; Maharani, Adinda Putri; br Barus, Cahaya Mutiara; Putri, Diajeng Amelia; Ningsih, Ayu Melati (PHILOLOGY Journal of English Language and Literature, 2024)
The current research juxtaposes the two assumptions regarding the black cat, which arose in America and Indonesia, and ties them to the short story by Edgar Allan Poe titled "The Black Cat." The objective of the current research is to pinpoint the myth or meaning pertaining to black cats in each nation. A qualitative method will be employed in this inquiry. Edgar Allan Poe's short story "The Black Cat" hires a myth or meaning that arose in the Americas, wherein black cats are thought to be witches.